(untitled) (Journal of Intellectual Property and Information Technology Law (JIPIT), 2022)
The Artist Resale Right (ARR) entitles a visual artist to a certain percentage of income generated from the resale of their artwork in the secondary market. Historically, resale royalty initiatives were motivated by a romantic notion that artists are so poor and in such a weak bargaining position that they deserve special legal protection. Arguments have since advanced from the notion of the ’starving artist’ to now citing the copyright protection deficiency that exists between the protection of multiple copy artists and visual artists. There has been advocacy from artists and politicians albeit not in collective voices for Botswana to codify ARR. This paper evaluates whether Botswana should provide for ARR in its laws and further guides lawmakers in considering such legislation. Specifically, this paper points out that many countries that have codified ARR have not implemented it. It attributes the lack of or delayed implementation of ARR to the information deficit, otherwise referred to as the asymmetry problem, that pervades the ARR practice. This asymmetry problem denies policymakers and other stakeholders a chance to establish the efficiency of ARR. The majority of arguments surveyed in this paper are at loggerheads, with each side raising strong valid points. This paper notes that the insignificant size of the Botswana art market is likely to eclipse the potential benefits promised by ARR. However, the authors conclude that Botswana should codify ARR based on the notion of redressing the copyright protection deficiency faced by visual artists as compared to other categories of copyright owners.